Germinability and pollen viability of four improved cultivars of palm oil under laboratory conditions (2018)
The success of assisted pollination in oil palm is essential for oil production, since it determines the amount of well-formed fruits; in this process, the pollen quality, expressed as viability and germinability, is of great importance. This work was carried out in the Salamanca Oleaginosas S.A. Laboratories, in order to determine the viability, germination and pollen tube growth of pollen grains of Guineensis, Amazon, Coari x Lame and Unipalma genotypes, stored during 0, 5, 15 and 30 days at room temperature, and -13 °C. Using an unrestrictedly randomized design with a factorial arrangement and four replications, the variables percentage of viability and germination, length and growth rate of the pollen tube were analyzed. Guineensis pollen had the highest germination and viability values, which ensure a good pollination efficiency, while the other cultivars had values below the recommended, although pollen tube growth of the few grains that germinated was similar to Guineensis.